Biohybrid Molecule‐Based Photocatalysts for Water Splitting Hydrogen Evolution. Issue 2 (20th February 2023) - Zheng, Tianfang; Li, Aijun; Han, Jiahong; Wang, Xiao‐Feng
Abstract: The problems of resource depletion and environmental pollution caused by the excessive use of fossil fuels greatly restrict the rapid development of human technology and industry, which has led to a high demand for the development of new and clean energy sources. Hydrogen, due to its high calorific value and environmentally friendly combustion products, is undoubtedly a very promising energy carrier. The current methods of industrial hydrogen production are mainly water electrocatalytic decomposition or fossil fuels conversion, which also results in the waste of other energy sources. Since only one‐step is involved during the conversion from solar to chemical energy and thus unnecessary energy waste is avoided, solar energy photocatalytic decomposition of water provides a more viable method for hydrogen production. The utilization of biohybrid molecules, which are widely available in nature and environmentally friendly, further reduce the cost of such photocatalytic systems. This Review discusses the research progress on hydrogen production using biohybrid molecules for photocatalytic hydrogen evolution. The basic reaction mechanism, general types and system structures about biohybrid molecule‐based photocatalysts are summarized. The current challenges and prospects in the research of water splitting hydrogen evolution by biohybrid molecules photocatalysts are presented. Abstract : Recent progress using biohybrid materials for photocatalytic water splitting hydrogen evolution, including the basic mechanism, types of photocatalysts, photocatalyst routes, etc., are discussed in this Review article. The prospects and difficulties are also discussed.